Architectural images and symbols of the regional identity of modern architecture in Kazakhstan - Aukhadiyeva, Laura; Karatseyeva , Tatsiana (Innovaciencia, 2022)
Introduction: The content of the research is devoted to identifying the architectural images and identity symbols of modern cities of the Republic of Kazakhstan. The relevance is the need to find new ways to create a regional architecture based on a set of principles of traditional art of building, modern innovations, capable of being not only unique in terms of the materials and structures used, but also being a part of the culture of Kazakhstan, part of the national, local self-identification. Materials and Methods: Aim of the study is a search for images and symbols of the city’s identity in Kazakhstan, as promising areas of the study and subsequent in the development of region. The basis of this research is made up of the theoretical works and a sociological survey and the features of the current city’s environment in Kazakhstan, images and architectural symbols of settlements, symbols of the country, were determined. Results and Discussion: The idea is substantiated that the search for representative images of buildings and structures play an important role, being a kind of “icons” of self-identification of citizens. Particular emphasis in the study was given to architectural images and identity symbols of the largest cities of Kazakhstan (Almaty and Nur-Sultan (formerly Astana)), identified through a sociological survey. Conclusions: The results of the research can be considered a prospect for more research of the architecture of the region. It should be noted that the hypothesis is confirmed, directions for further study have been outlined.